Openness and Attention in the New Economy of the Social Media Era - Ardilla, Yunda Presti (Inter Komunika, 2023)
Abstract. Changes in the communication media in the form of social and business interactions have brought people to changes in the new economic ecosystem, especially social media. Social media offers an economic ecosystem called attention economy. In contrast to the money economy, attention is more abstract and requires steps for financialization. However, it remains a rare and contested item in the digital world. Various ways are used to get the attention. One of them is by using openess. This article applies a qualitative approach with the descriptive case study strategy and interviews with selected informants in order to describe how a non-profit institution, in this case the Lembaga Pengelola Dana Pendidikan Republik Indonesia (LPDP RI) / Educational Fund Management Institution of the Republic of Indonesia, applied openess to social media to attract attention from its followers. The data were collected by in-depth interviews. This technique works by recording verbal statements of the research subjects and involving other persons to limit word flows, which are submitted by questions. As a result, the non-profit institution did not fully implement openess in social media. This resulted in non-optimal attention from the followers, namely stake holders, scholarship recipients, prospective scholarship recipients and public.  It is suggested to other non-profit institutions to continuously apply openess in order to obtain benefits in the form of attention optimally.